PENGARUH PENGGENANGAN TERHADAP PERTUMBUHAN VEGETATIF CABAI - Safrizal Safrizal (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2008)
The Effect of Water Logging on Vegetative Growth of Chilli Safrizal1, Edi Santosa2, dan Bakhtiar3 1 Departemen Agronomi Fakultas Pertanian UNIMAL Lhokseumawe. Jl. Tgk Chikditiro N0 26 Lancang Garam Lhokseumawe.Email :safrizalsarong@yahoo.com.2 Departemen Agronomi dan Hortikultura, Fakultas Pertanian, IPB. Jl. Meranti, Kampus IPB Darmaga-Bogor, 16680. Email : edi_today@yahoo.com.3 Program Studi Agrotekhnologi, Fakultas Pertanian UNSYIAH Banda Aceh.Email :bakhtiarbasyah@yahoo.com. ABSTRACT Generally, chilli grows at dry season, but only offers low price of the yield. To obtain high price of the yield, usually farmers grow this crop at out of season, i.e. wet season. Wet season, however, has more limiting factors to increase the yield, such as water logging. The aim of this study was to understand the resistance of plant to water logging. Seedlings at 21 days of age were planted in plastic container. The result indicated that full water logging and half water logging inhibited vegetative growth of chilly. However, the seedlings were survive until 3 week of logging. Full water logging caused horizontal growth of roots. Full water logging also caused increase of chlorophyl b, antocianin, and carotenoid, but decrease of chlorophyl a.